Political Communication Strategy Of PDI Perjuangan(Descriptive Qualitative Study The Bapilu In Winning The Vote In 2014 Legislative Elections In Pasar Kliwon Sub-District Of Surakarta City) - Al Habsyi, Haniah Fahmi; , Nur Latifah Umi Satiti, MA; , Palupi, M.A (2015)
PDI Perjuangan is one of the major politics parties in Indonesia. In facing the 2014 legislative election, it should prepare a good political communication strategy to achieve the vote's acquisition, including in Surakarta city. Pasar Kliwon is an area which is famous as the majority ethnic Arab Muslims in Surakarta. In that district which is part of the electoral district 5, the party that is not adhered to the principles of Islam gets increased votes in 2014 legislative election compared with 2009 legislative election. The purpose of the study is to know the political communication strategies used by the PDI Perjuangan, in the winning vote of this region. The research subject is the cadre of PDI Perjuangan, which consists of the Chairman of Bapilu also two elected legislators in the sub-district of Pasar Kliwon and the data collection method is used interviews and documentation. The analysis technique used is descriptive qualitative analysis. The results obtained indicate that there are several of political communication strategies used, such as: a dialogic campaign, opinion leaders, delivering rumored program, reminding the success of the program, and building image.